The grammatical terms Al-Musnad, Al-Musnad ʾIlayhi and al-ʾisnād - Levin, Aryeh (JAOS, 1981)
In the works of the Arab grammarians we find two essential views of the musnad and the musnad ʾilayhi: the ancient view held by Sībawayhi (eighth century) and most likely by al-Mubarrad (ninth century), and the later view which prevails in the sources beginning with the tenth century. According to Sībawayhi and al-Mubarrad, both the musnad and the musnad ʾilayhi are two indispensable parts of the sentence. Sībawayhi's criterion for the distinction between the musnad and the musnad ʾilayhi is their sequence in the sentence, and not their syntactic function: the musnad is the first indispensable part of the sentence, and the musnad ʾilayhi is the second indispensable part. In the later sources, from the tenth to the fifteenth centuries, the attitude to the musnad and the musnad ʾilayhi is completely different from that of Sībawayhi. In these sources the term musnad denotes the predicate and the term musnad ʾilayhi denotes the subject of all types of sentences. In these sources the criterion for the distinction between the two terms is the syntactic function of the musnad and the musnad ʾilayhi respectively, while the word order becomes irrelevant. In the same sources, ʾasnadahu ʾilā occurs as a technical grammatical expression meaning "to assign a predicate to a subject." The maṣdar of ʾasnada ʾilā, which is al-ʾisnād ʾilā or al-ʾisnād denotes, in these sources, "the assignment of the predicate to the subject."